Urban Regeneration and Changes Driven by Tourism and the ‘Skopje 2014’ Project - Iliev, Dejan (Accent Publisher, 2021)
The current paper explores the relationship between urban regeneration, tourism and culture, and offers a common approach that each of these three concepts can bring. The paper proposes and develops a new and integrated conceptual analytical framework. The analysis uses the example of the capital Skopje, which provides a suitable framework for interpreting the process. The study uses combined research methods and analysis to obtain a critical synthesis. Skopje has catalyzed a new example of urban regeneration driven by tourism and the ‘Skopje 2014’ project. The results show that, except for the old city’s core, which was generally refurbished with the ‘Skopje 2014’ project, new tourist values were also promoted in other peripheral municipalities of the city. The number, spatial concentration and nationality of foreign tourists have changed in the analyzed period. As well, the findings indicate changes in the geography and business of hotels/accommodation establishments and their increasing use in recent years. This study fits into the theoretical debate on the determinants of tourism/culture-led urban regeneration and provides appropriate theoretical contributions to literature, as well as a set of recommendations that can be useful for public sector authorities and policymakers.
Keywords: urban regeneration, tourism, culture, place, transformation, Skopje